TAFSIR MAQHASIDI SEBAGAI BASIS ETIKA LINGKUNGAN: Studi Ekosufisme atas QS. Al-Baqarah [2]: 30 - Bagus Gunawan Setyo (LPPM STAI Nida El-Adabi, 2025)
This study aims to explore Islamic environmental ethics in QS. Al-Baqarah [2]: 30 through a maqashidi interpretation and an ecosufism perspective. This approach departs from the understanding that today’s ecological crisis is not merely driven by technical or economic factors, but also by a moral and spiritual collapse in how human beings treat nature. The research method employs library research by reviewing classical and contemporary tafsir literature, maqashid al-shari‘ah discourse, hadith texts, and relevant academic studies. The findings reveal that the concept of khalifah (vicegerency) in QS. Al-Baqarah [2]: 30 contains an ecological mandate aligned with the objectives of Islamic law, particularly in preserving life, posterity, safety, and environmental balance. The ecosufism perspective strengthens spiritual awareness by positioning nature as divine signs that deserve respect, care, and protection. This study concludes that integrating maqashidi tafsir and ecosufism produces not only a textual-based ecological ethic but also practical implications for sustainable programs such as zero-waste movements, water conservation, reforestation, eco-Islamic pedagogy, and environmental advocacy. Thus, Islam offers a comprehensive ecological paradigm—rational, spiritual, and applicable—to respond to modern environmental destruction and to build a sustainable civilization.